Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Terhadap Kemampuan Pemahaman Konsep Matematis Peserta didik Kelas XI IPA SMA Adabiah Padang Tahun Ajaran 2019/2020 - Salsabilla Rahmah (Jurnal Edukasi dan Penelitian Matematika, 2020)
--- understanding of mathematical concepts skills are one of the basic abilities that must be possessed by students. However ,in reality the understanding of mathematical skill of class XI science students in SMA Adabiah Padang are still low and learning process is still oriented towards teacher centered. The solution used to over come these problems are to use cooperative learning model; Student Team Achievement Division (STAD) that will greatly improve student’s understanding of mathematical concepts skill. So that students are able to understand the idea of the topic. The purpose of the research was to describe whether  the understanding of mathematical concepts of grade XI Science student of SMA Adabiah Padang that taught using cooperative learning model; Student Team Achievement Division (STAD) were better than student who taught using direct learning.The type of the research is a quasi experiment with the design of Randomized Control-Group Only Design. The sample in this research was class XI Science 2 as the experimental class and Xi Science 3 as the  control class. The instruments used to collect informayion in this research were final test and quizzes.The results of the research that has been conducted show that students who taught using the cooperative learning; Student Team Achievement Team Division (STAD) model can improves their understanding of  mathematical concept skills. Based on the test P-value=0,007 is obtain. Because the P-value <α=0,05 then reject H0. Thus, it can be concluded that students who taught using the cooperative learning ; Student Team Achievement Division (STAD) have better mathemtical understanding of mathematical concept skills than students who taught using the direct learning model in class XI science of SMA Adabiah Padang.Keywords--- direct learning, understandng of mathemathical concepts skills, STAD learnng model.